Research on logistics carbon emissions under the coupling and coordination scenario of logistics industry and financial industry. - Lu Wang (PLoS ONE)
In order to measure the impact of the degree of coupling and coordination between logistics and financial industries on the carbon emissions of the logistics industry, a comprehensive evaluation index system for the logistics-financial industry from 2007 to 2017 was constructed, which was calculated using the multi-objective linear weighting method; and a combination of logistics and financial industry was constructed. The panel smooth conversion model of coordination degree and carbon emission of logistics industry. The empirical results show that the coupling coordination degree of logistics and financial industry in China's 30 provinces is mostly in primary and medium coordination, and only a few provinces are on the verge of imbalance; the coupling coordination degree in the eastern region is overall moderate coordination, and the overall coordination degree in the central and western regions It is the primary coordination; with the growth of GDP per capita, the degree of coupling and coordination between the logistics and financial industries has promoted the increase of carbon emissions in various regions, but the promotion effect is an inverted U-shaped trend that first increases and then decreases.